Spasialisasi dan Konglomerasi Media Pada Kelompok Kompas Gramedia - Simamora, Elisabeth Rotua (Jurnal The Messenger, 2016)
Spatialization is a part of the political economy. Media realize theta it is the process of  overcoming the constraints of space and time through its two forms of renewal of corporate power, that is horizontal and vertical concentration. The growth of media is becoming the trend of economy and politic in the media industry and expanding the corporae ownership. By having a literatures study used, the writer found that mass media development nowdays is not only the company's abilities to provide and satisfy the information and entertainment needs which match the society needs, however it also developes the other business interest s orientations.